MARTINI coarse‐grained model for poly‐ε‐caprolactone in acetone‐water mixtures. (8th May 2020) - Lavino, Alessio D.; Carbone, Paola; Marchisio, Daniele
Abstract: In this work we present the development of a MARTINI‐type coarse‐graining (CG) model for poly‐ε‐caprolactone (PCL) dissolved in a solvent binary mixture of acetone and water. A thermodynamic/conformational procedure is adopted to build up the CG model of the system, starting from the standard MARTINI force field. The single CG bead is parametrized upon solvation free energy calculations, whereas the conformation of the whole polymer chain is optimized using the radius of gyration values calculated at different chain lengths. The model is then able to reproduce the correct thermodynamics of the system, as well as the conformation of single PCL chains, especially in pure water and acetone. The results obtained here are then used to simulate the interactions between multiple longer PCL chains in solution. The model developed here can be used in the future to achieve deeper insight into the dynamics of the polymer self‐assembly.